Under the Skin: A Theatrical Exploration of Art, Politics, and Fieldwork Dynamics - Svašek, Maruška (Lidé města, 2022)
Under the Skin is a play that explores art production in state-socialist Czechoslovakia during the normalization period. It investigates the slippery meaning of the word politics in relation to totalitarianism and performance art, and discusses how internalized taken-for-granted social rules can be made evident through artistic inquiry. The script offers insights into the improvisational nature of fieldwork, and invites producers and consumers of ethnographies to reflect on the ethical and affective dimensions of anthropological labour and knowledge production.